Sustainable livelihoods and youth empowerment in informal settlements: the case of Lindelani informal settlement, Ekurhuleni Metropolitan Municipality - Mabona, Rachel L. (My University, 2019)
High unemployment rates of 38,2% of youth at age 15-34 in South Africa build substantial difficulties in young people’s ability to become self-reliant. The unemployment of youth remains the biggest challenge in South Africa making youth vulnerable to crime, drugs and violence. The challenges facing the youth call for urgent expansion of livelihood opportunities, through supportive interventions that are based on an understanding of their circumstances. Youth in informal settlements are particularly vulnerable to unemployment and poverty, ill health, and social exclusion and marginalisation than those living in better-located areas. They live in areas where they do not receive basic services. The environment the poor youth life inputs them in vulnerable situations. Informal settlements are prejudiced when it comes to youth support, job creation and policy interventions. Youth livelihoods in the informal settlements are not adequately addressed by research conducted on sustainable livelihoods. Research mainly is done on household and rural livelihoods. The main aim of this study is to understand the livelihoods of youth living in informal settlements as a basis for formulating interventions that are appropriate and well-targeted. By understanding the livelihood strategies and vulnerability of youth in informal settlements, interventions may stand a better chance of promoting poverty reduction, and social cohesion and improving their living conditions. Lindelani informal settlement situated in the urban periphery of Benoni Ekurhuleni Metropolitan Municipality was selected as a case study because the area is not developed, people are living under bad conditions with limited basic services. Again, there is no research done on this informal settlement. This study adopted a qualitative approach to research in order to explore the experiences of the youth in informal settlements. In-depth interviews conducted with 15 young men and women aged 19-35 years to fully understand their livelihoods. The sustainable livelihood approach (SLA) suggested by Chambers and Conway (1992) was used as the framework for obtaining and analysing information about the current livelihoods of the youth. The SLA assists in assessing the different capitals or assets that underpin the livelihoods of the youth. For this study, the most significant forms of capital were human capital (i.e. issues of education, skills and health), financial capital (i.e. issues of income), physical capital (i.e. housing) and social capital (i.e. social relations and social networks). To succeed in fighting poverty, it is imperative that livelihoods remain sustainable and/ or be able to cope with and recover from stresses and shocks. In addition, the youth capabilities and assets must be enhanced or developed both now and, in the future, without undermining the natural resource 2 base strengthening the informal sector through skills development can provide employment to the youth and improve income for sustainable economic and social development and thus reducing poverty. The study found that the youth from Lindelani informal settlement are faced with multiple socio-economic challenges. In order to survive, they survived by involving themselves in informal activities, such as tuck-shop, crèche, hair salon, illegal mining, fixing bicycles, shoe repairing and other piece jobs like painting, tiling and lawn mowing. These informal activities are augmented with government support grants received by either parents and children, that is child support grants. While there are municipal programmes available they are not directed to the needs of those living in informal settlements. It is recommended that programmes designed to alleviate poverty and strengthen their self-esteem are necessary. The study recommended that in the absence of the non-governmental organisations (NGOs) the youth leaders from different political organisations and the ward committee prepare a detailed understanding of the youth in Lindelani using the SLA in order to assist them appropriately. The youth in informal settlements need access to decent housing with better infrastructure and basic services, that are situated where economic opportunities are available.
A research report submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, in fulfilment of the requirements for the degree of Masters of the Built Environment in Housing.
Keywords: Squatter settlements--South Africa; Youth, Black--South Africa; Low-income housing--South Africa